Supporting Women’s Economic Engagement in the Turkish Cypriot Economy : Entry Points and Proposed Approaches - World Bank (Washington, DC, 2022)
This activity, which is part of the World Bank’s European Commission (EC) - funded multisectoral engagement in the Turkish Cypriot community (TCc), aims to support the efforts to promote women’s economic engagement, in particular by identifying constraints and required support for female self-employment and entrepreneurship in the TCc. Equality between men and women is a fundamental principle of the European Union and supporting women’s economic empowerment in the TCc is therefore directly linked to advancing the European Union’s (EU’s) gender acquis. The TCc has made strides in narrowing gender gaps in education; even reversing them for younger generations, including in tertiary education. The female labor market in the TCc is characterized by low participation and low employment rates. Investing in women’s economic engagement is a priority for the TCc’s economic recovery and boost its resilience to shocks. Women-led enterprises (WLE) are relatively small and focus on low value added production, mainly concentrated in the service sector, and are made up of family-run micro and small enterprises.